Affective Scaffolds, Expressive Arts, and Cognition - Maiese, Michelle (Frontiers in Psychology, 2016)
Some theorists have argued that cognitive agents engineer their environment to sustain and amply their cognitive abilities, and also that elements of the surrounding world sometimes play a crucial role in evoking and sustaining emotion. Such insights raise an interesting question about the relationship between cognitive and affective scaffolding: in addition to enabling the realization of specific affective states, can an affective niche also enable the realization of certain cognitive capacities? In order to gain a better understanding of this relationship between affective scaffolding and cognition, I will examine the use of expressive arts in the context of psychotherapy and peacebuilding. In these settings, environmental resources and interpersonal scaffolds not only evoke emotion and encourage the adoption of particular bodily-affective styles, but also support the development of capacities for self-awareness and interpersonal understanding. These affective scaffolds play a crucial role in therapy and peacebuilding, in fact, insofar as they facilitate the development of self-knowledge, enhance capacities associated with social cognition, and build positive rapport and trust among participants. I will argue that this is because affectivity is linked to the way that subjects frame and attend to their surroundings. Insofar as the regulation and modulation of emotion goes hand in hand with opening up new interpretive frames and establishing new habits of mind, affective scaffolds can contribute significantly to various modes of cognition.